Developmental remodelling of Drosophila flight muscle sarcomeres: a scaled myofilament lattice model based on multiscale morphometrics - Péter Görög; Tibor Novák; Tamás F. Polgár; Péter Bíró; Adél Gutheil; Csaba Kozma; Tamás Gajdos; Krisztina Tóth; Alexandra Tóth; Miklós Erdélyi; József Mihály; Szilárd Szikora (Open Biology)
The indirect flight muscle is a widely used model for studying sarcomere structure and muscle development due to its extremely regular architecture. Nevertheless, precise measurement of the basic sarcomeric parameters remains a challenge even in this greatly ordered tissue. In this study, we identified several factors affecting measurement reliability and developed a software tool for precise, high-throughput measurement of sarcomere length and myofibril width. The accuracy of this new tool was validated against simulated images and blinded manual measurements. To extend the scope of this morphometric analysis to the sub-sarcomeric scale, we used electron and super-resolution microscopy to quantify myofilament number and filament length during myofibrillogenesis. Our findings revealed the dynamics of thin and thick filament elongation, as well as the addition of myofilaments at the sarcomere periphery during myofibrillogenesis. We precisely measured the dimensions of the Z-disc, I-band and H-zone during development, enabling us to construct refined models of sarcomere growth at the level of individual myofilaments, providing a spatial framework for interpreting nanoscopic localization data. These models deepen our understanding of sarcomere growth and lay the groundwork for future studies on the molecular mechanisms driving myofilament elongation and assembly.